Peculiarities of determining the duration of a lethal mechanical trauma using cortisol/cortisone rate in human adrenal tissue. - Bilyakov, A. M. (Морфологія / Morphologia / Morfologìâ, 2013)
Criteriafordeterminingthedurationofalethalmechanicaltraumawereestablishedusingtherateofcortisol/cortisonecontentsinhumanadrenaltissue.Itisdeterminedthatifcortisol/cortisonerateinhumanadrenaltissueismorethan 1.8, itcanbestatedthatthepersondidnotdie immediatelyafterthetraumabutashortperiodoftimelater (from several to some tens minutes) or 1-2 hours after the injury.